2009
DOI: 10.1002/anie.200900002
|View full text |Cite
|
Sign up to set email alerts
|

Suprapolymer Structures from Nanostructured Polymer Particles

Abstract: Divide and conquer: Polymer nanoparticles with phase-separation structures prepared with block copolymers and homopolymer blends were used to fabricate unique suprapolymer structures by cross-linking one polymer moiety and dissolving the other (see scheme; PI = polyisoprene, PSt = polystyrene).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 23 publications
4
95
1
2
Order By: Relevance
“…52,55 We have reported block copolymer nanoparticles with various microphase-separated structures such as unidirectionally stacked lamellar, onion-like and cylindrical structures prepared by adding a poor solvent into a block copolymer solution and subsequently evaporating the good solvent (self-organized precipitation; SORP). [57][58][59][60][61] We have also reported that symmetrical block copolymers with high molecular weights form complex microphase-separated structures in nanoparticles induced by the frustration of the 3D confinement effect. 55 Frustrated phase-separated structures in nanoparticles strongly depend on the ratio of particle diameter to the equilibrium domain spacing of microphase-separated structures.…”
Section: Introductionmentioning
confidence: 94%
“…52,55 We have reported block copolymer nanoparticles with various microphase-separated structures such as unidirectionally stacked lamellar, onion-like and cylindrical structures prepared by adding a poor solvent into a block copolymer solution and subsequently evaporating the good solvent (self-organized precipitation; SORP). [57][58][59][60][61] We have also reported that symmetrical block copolymers with high molecular weights form complex microphase-separated structures in nanoparticles induced by the frustration of the 3D confinement effect. 55 Frustrated phase-separated structures in nanoparticles strongly depend on the ratio of particle diameter to the equilibrium domain spacing of microphase-separated structures.…”
Section: Introductionmentioning
confidence: 94%
“…1b and c) and dark field (Fig. 1d) show that the inner porous structure of the sample exhibits a radial distribution of pore channels with a diameter of 2.7 ± 0.4 nm; this pore dimension is in accordance with the expected porosity produced by using CTAC as template [16]. From the plot profile of the images we have also calculated the pore walls dimension as 3.1 ± 0.4 nm.…”
Section: Resultsmentioning
confidence: 71%
“…In general, for preparation of rings via coffee stain only micro or nanoparticles and never mesoporous beads have been used. The potential advantages of the use of mesoporous beads are related to the large area provided by this class of materials together with the wide tunability of the pore surface chemistry [15,16]; several type of organic functions, in fact, have been already grafted on the pore surface to induce specific properties, from drug delivery up to fluorescent properties [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…8A). [123,124] Intriguingly, the resulting particles exhibited a diversity of microphase separation nanostructures both on the surfaces and within the inner cores; the phase separation structures were determined by the stoichiometric ratio of PS to polyisoprene. Cohen Stuart et al have created Janus micelles from two block polymers, poly(acrylic acid)-block-polyacrylamide and poly(2-methylvinylpyridinium iodide)-block-poly(ethylene oxide) by combining associative and segregative phase separation; the micelles are composed of poly(acrylic acid) and poly(2-methylvinylpyridinium iodide) coacervate cores with one coronal hemisphere of polyethylene oxide and the other of polyacrylamide.…”
Section: Microphase Separationmentioning
confidence: 99%
“…a) Dark-field scanning TEM image; b) cross-sectional TEM image; c) schematic model of the PS-PI-30 nanoparticles. Reproduced with permission from Reference[123], copyright 2009 Wiley-VCH. B) Average diameter 2R of the cross-linked PS particles as a function of time after adding styrene to the mixture.…”
mentioning
confidence: 99%